Implementasi Peraturan Menteri Agama No 20 Tahun 2019 Pasal 5 Ayat (3) Tentang Pemeriksaan Dokumen Pencatatan Perkawinan di KUA Margaasih - Ibtihal Khalda; Ramdan Fawzi; Yandi Maryandi (Bandung Conference Series: Islamic Family Law, 2023)
Abstract. In the Marriage Registration section, further document inspection is regulated in Article 5 paragraph (3) "The Head of the KUA District/ Penghulu/ PPN LN conducts an examination of marriage documents by presenting the prospective husband, prospective wife, and guardian to ascertain whether or not there is a marriage certificate." Based on the article above, it is clear that when registering a marriage, the bride and groom are required to be present and bring their guardian, with the aim of checking whether there are obstacles to getting married or not. This study aims to find out how the implementation of the Minister of Religion Regulation No. 20 of 2019 concerning examining marriage registration documents at the KUA Margaasih. The research uses qualitative methods with a normative juridical approach, field data types (Field Research) and library data. Methods of data collection with interviews and retrieval. The results of this study are that the implementation of the minister of religion regulation No. 20 of 2019 article 5 paragraph (3) concerning examining marriage registration documents at KUA Margaasih has not yet implemented this regulation, especially in examining marriage guardians when the bride and groom register at the KUA, the causative factor of religious regulation No. 20 article 5 paragraph (3) concerning marriage marriages has not been treated because the bride and groom do not understand or know these religious regulations, then the KUA itself has not provided socialization to the prospective bride and groom regarding the guardian's wedding ceremony when carrying out the marriage. Abstrak. Dalam Pencatatan Perkawinan bagian pemeriksaan dokumen lebih lanjut diatur dalam pasal 5 ayat (3) “Kepala KUA Kecamatan/ Penghulu/ PPN LN melakukan pemeriksaan terhadap dokumen nikah dengan menghadirkan calon suami, calon istri, dan wali untuk memastikan ada atau tidak adanya untuk menikah.” Berdasarkan pasal diatas jelas bahwa ketika mendaftarkan nikah calon pengantin diharuskan hadir dan membawa wali nikahnya, dengan tujuan untuk pemeriksaan apakah ada halangan menikah atau tidak. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi peraturan menteri agama no 20 tahun 2019 tentang pemeriksaan dokumen pencatatan perkawinan di KUA Margaasih. Penelitian menggunakan metode kualitatif dengan pendekatan yuridis normatif, jenis dari data lapangan (Field Research) dan data Pustaka. Metode pengumpulan data dengan wawancara dan dokumentasi. Hasil penelitian ini bahwa implementasi peraturan menteri agama no 20 tahun 2019 pasal 5 ayat (3) tentang pemeriksaan dokumen pencatatan perkawinan di KUA Margaasih belum begitu diterapkan peraturan tersebut khususnya dalam pemeriksaan terhadap wali nikah pada saat calon pengantin melakukan pendaftaran ke KUA, faktor penyebab peraturan menteri agama No 20 pasal 5 ayat (3) tentang pemeriksaan pencatatan perkawinan ini bekum di terapkan karena calon pengantin yang belum paham atau mengetahui terhadap peraturan menteri agama tersebut, kemudian dari pihak KUA sendiri belum memberikan sosialisasi terhadap calon pengantin terhadap pentingnya wali dihadirkan pada saat melkukan pendaftaran perkawinan.